2014
DOI: 10.3140/bull.geosci.1467
|View full text |Cite
|
Sign up to set email alerts
|

A remarkable illaenid trilobite from the Middle Ordovician of Morocco

Abstract: Illaenid trilobites were relatively scarce in south-polar peri-Gondwanan areas during the Ordovician, with all their African occurrences restricted to the Middle and Upper Ordovician of Morocco. At a specific level, only the Bohemian form Ectillaenus benignensis (Novák) has been positively identified from the Middle Ordovician of that region. In the present work we add the discovery of the new form Caudillaenus nicolasi gen. et sp. nov., occurring in a single bed of late Darriwilian 2 age within the Taddrist F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 8 publications
0
21
0
Order By: Relevance
“…This report was based on a single specimen, then belonging to the private collection of Laurent Lacombe that is now registered and deposited in the University Lyon 1 collections as UCBL-FSL 712001. However, more precise information obtained in late 2013 from Laurent Lacombe and Patrick Catto (who together collected this specimen and another one, UCBL-FSL 712000, in the mid 2000s) did not confirm this age and geographic origin, but pointed out that the two specimens were indeed collected from the same locality (Battou) and level (Taddrist Formation) described in Rábano et al (2014).…”
Section: Geological Setting and Stratigraphymentioning
confidence: 99%
See 4 more Smart Citations
“…This report was based on a single specimen, then belonging to the private collection of Laurent Lacombe that is now registered and deposited in the University Lyon 1 collections as UCBL-FSL 712001. However, more precise information obtained in late 2013 from Laurent Lacombe and Patrick Catto (who together collected this specimen and another one, UCBL-FSL 712000, in the mid 2000s) did not confirm this age and geographic origin, but pointed out that the two specimens were indeed collected from the same locality (Battou) and level (Taddrist Formation) described in Rábano et al (2014).…”
Section: Geological Setting and Stratigraphymentioning
confidence: 99%
“…Unfortunately, original top or bottom of our cyclocystoid concretions from this layer has not been recorded by any of the collectors, perhaps because many concretions were already weathered out and lying on the surface of this sloping outcrop. Rábano et al (2014) suggested that the levels containing fossiliferous concretions belong to the Didymograptus murchisoni graptolite Biozone (Gutiérrez-Marco et al, 2003), which Figure 2. Chronostratigraphical chart for the Ordovician, indicating the level that provided the studied specimens.…”
Section: Geological Setting and Stratigraphymentioning
confidence: 99%
See 3 more Smart Citations